The risk of cardiac events in patients receiving immune checkpoint inhibitors: a nationwide Danish study - D'Souza, Maria; Nielsen, Dorte; Svane, Inge Marie; Iversen, Kasper; Rasmussen, Peter Vibe; Madelaire, Christian; Fosbøl, Emil; Køber, Lars; Gustafsson, Finn; Andersson, Charlotte; Gislason, Gunnar; Torp-Pedersen, Christian; et al. (European heart journal, 2021)
The study aimed to estimate the risk of cardiac events in immune checkpoint inhibitor (ICI)-treated patients with lung cancer or malignant melanoma. The study included consecutive patients with lung cancer or malignant melanoma in 2011-17 nationwide in Denmark. The main composite outcome was cardiac events (arrhythmia, peri- or myocarditis, heart failure) or cardiovascular death. Absolute risks were estimated and the association of ICI and cardiac events was analysed in multivariable Cox models. We included 25 573 patients with lung cancer. Of these, 743 were treated with programmed cell death-1 inhibitor (PD1i) and their 1-year absolute risk of cardiac events was 9.7% [95% confidence interval (CI) 6.8-12.5]. Of the 13 568 patients with malignant melanoma, 145 had PD1i and 212 had cytotoxic T-lymphocyte-associated protein-4 inhibitor (CTLA-4i) treatment. Their 1-year risks were 6.6% (1.8-11.3) and 7.5% (3.7-11.3). The hazard rates of cardiac events were higher in patients with vs. without ICI treatment. Within 6 months from 1st ICI administration, the hazard ratios were 2.14 (95% CI 1.50-3.05) in patients with lung cancer and 4.30 (1.38-13.42) and 4.93 (2.45-9.94) in patients with malignant melanoma with PD1i and CTLA-4i, respectively. After 6 months, HRs were 2.26 (1.27-4.02) for patients with lung cancer and 3.48 (1.91-6.35) for patients with malignant melanoma and CTLA-4i. Among patients with lung cancer and malignant melanoma, ICI treated had increased rates of cardiac events. The absolute risks were higher in these data compared with previous pharmacovigilance studies (e.g. 1.8% peri-/myocarditis 1-year risk).